Absorption of calcium and magnesium in patients with intestinal resections treated with medium chain fatty acids. Issue 6 (1st June 2000) - Haderslev, K V; Jeppesen, P B; Mortensen, P B; Staun, M
Abstract : BACKGROUND: Steatorrhoea is associated with increased faecal loss of calcium and magnesium. Medium chain C8-C10 triglycerides (MCTs) improve fat absorption in patients with small bowel resections but the effects on intestinal absorption of divalent cations are not clear. AIM: To assess the effect of dietary replacement of long chain triglycerides (LCTs) with MCTs on calcium and magnesium absorption in patients with small bowel resections. PATIENTS: Nineteen adult patients with a remaining small intestine averaging 171 cm (range 50–300). METHODS: In a crossover design, patients were randomised to two high fat diets (10 MJ/day, 50% as fat) for four days each separated by one day of washout. Diets were prepared in duplicate and were based on either LCT (LCT period) or equal quantities of LCT and MCT (L/MCT period). Metabolic balances were calculated during the last three days of each period. RESULTS: Mean stool volume increased significantly with the L/MCT diet and was 336 ml more than that with the LCT diet (95% confidence interval of mean difference, 26–649 ml). There was no significant change in the net absorption of calcium and magnesium between the two diets. On average, percentage calcium absorption was 8.6% with the LCT diet and 12.5% with the L/MCT diet. Mean percentage magnesium absorption was 5.4% with the LCT diet and 2.9% with the L/MCT diet. CONCLUSIONS: Dietary replacement of 50% long chain triglycerides with medium chain triglycerides in small bowel resected patients increased faecal volume significantly. No changes in the intestinal net absorption of calcium and magnesium were demonstrated.